Population genomics reveals possible genetic evidence for parallel evolution of Sebastiscus marmoratus in the northwestern Pacific Ocean. Issue 9 (4th September 2019) - Xu, Shengyong; Yanagimoto, Takashi; Song, Na; Cai, Shanshan; Gao, Tianxiang; Zhang, Xiumei
Abstract : Abstract : Understanding patterns of population diversity and structuring among marine populations is of great importance for evolutionary biology, and can also directly inform fisheries management and conservation. In this study, genotyping-by-sequencing was used to assess population genetic diversity and connectivity of Sebastiscus marmoratus . Based on 130 individuals sampled from 10 locations in the northwestern Pacific Ocean, we identified and genotyped 17 653 single-nucleotide polymorphisms. The patterns of genetic diversity and population differentiation suggested that the Okinawa Trough might be the ancestral centre of S. marmoratus after the Last Glacial Maximum. A shallow genetic structure was observed among sampled populations based on the implemented structuring approaches. Surprisingly, we detected genetic homogeneity in two population pairs (i.e. Xiamen–Niigata and Zhuhai–Iki Island), in which populations have large geographical and latitudinal intervals. Population structure and allele frequency distribution based on outlier loci also mirrored the observed genetic homogeneity in the above-mentioned population pairs. Integrated with biological, environmental and genomic data, our results provide possible genetic evidence for parallel evolution. Our study also provides new perspectives on the population structure of S. marmoratus, which could have important implications for sound management and conservation of this fishery species.